1979
DOI: 10.1016/0370-2693(79)91253-x
|View full text |Cite
|
Sign up to set email alerts
|

Further measurements of parity non-conservation in inelastic electron scattering

Abstract: We have extended our earlier measurements of parity violating asymmetries in the inelastic scattering of longitudinally polarized * Work supported by the Department EY-76-C-03-0515.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
139
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(143 citation statements)
references
References 4 publications
4
139
0
Order By: Relevance
“…The growth for x B near one is a result of the relatively quicker fall off with x B of the pdfs; the twist-four contribution in the numerator is falling less quickly in this region. 2 One can also perform this analysis with alternative parametrizations of the structure function moments. This was done in Ref.…”
Section: Model Estimates Of Higher Twist Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth for x B near one is a result of the relatively quicker fall off with x B of the pdfs; the twist-four contribution in the numerator is falling less quickly in this region. 2 One can also perform this analysis with alternative parametrizations of the structure function moments. This was done in Ref.…”
Section: Model Estimates Of Higher Twist Effectsmentioning
confidence: 99%
“…In the 1970s parity-violating deep-inelastic scattering (PVDIS) of longitudinally polarized electrons from deuterium played an important role in confirming the standard model (SM) of particle physics [1][2][3]. The asymmetry,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 70's, Prescott et al 1,2 showed, by measuring the non-zero asymmetry A LR = (σ L − σ R )/(σ L + σ R ) for polarized electron-deuterium deep inelastic scattering, that the weak neutral current violates parity . The experiment also set limits on the dependence of A LR on the variable y ≡ (E − E )/E, which ruled out models invented to explain the negative results of the early atom parity violation (APV) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was originally used to verify the nature of the weak neutral-current [1,2], and more recently has been used to bound the size of the strange quark contribution to the nucleon form factors [3,4,5,6,7,8], verify the existence of a "neutron-skin" in 208 Pb [9,10], and to do precision tests of the Standard Model of particle physics [11,12]. Asymmetries measured in experiments so far have ranged from ∼200 parts-per-million (ppm) down to ∼0.2 ppm, depending on the physical process and kinematics.…”
Section: Introductionmentioning
confidence: 99%